Tinjauan Pelepasan Informasi Rekam Medis Berdasarkan Aspek Hukum Keamanan dan Kerahasiaan Rekam Medis untuk Pendidikan di RSUD Sleman - Futari Ayu Istikomah; Feby Erawantini; Dony Setiawan Hendyca Putra (Politeknik Negeri Jember, 2020)
Regional general hospital of sleman (RSUD) is a hospital located in Sleman Regency with type B education. As a teaching education, Sleman District Hospital often borrows medical records for research (Education) related to the release of medical record information with third parties necessary. Because the character of medical record documents and their contents are confidential, the hospital must guarantee the confidentiality of the contents of the medical record file and legal protection for patients and hospitals. This research was aimed to find out how the release of medical record information based on legal aspects of the security and confidentiality of medical records for education in Sleman Hospital. This type of research is qualitative by collecting data using interviews, observation and documentation. The results of research at the Sleman Hospital in the application of releasing medical record information for educational purposes in the Sleman Hospital are still not by existing regulations related to the unavailability of expedition books or medical record file borrowing books where the book is very important in knowing the existence of medical record files that come out. And a special place for researchers when researching medical record files is not yet available due to limited space in the medical record unit of Sleman District Hospital.